Injection of a Bone Substitute in the Treatment of Unicameral Bone Cysts. (5th January 2023) - Sivakumar, B.; An, V. V. G.; Dobbe, A.; Drynan, D.; Little, D.
Abstract : Background . Simple bone cysts are benign bony lesions. Treatment strategies are varied for this particular pathology. It remains controversial as to what the ideal treatment strategy is. Recently, bony substitute injections have emerged as a potential option for treatment. This paper aimed to describe our institution's experience in using bony substitute injections to treat unicameral bone cysts. Methods . A retrospective review of consecutive patients over an 84-month period at a tertiary paediatric hospital was performed. Information regarding patients' presentation, diagnosis, and management was recorded and summarised. Results . A total of 15 patients were included in our study, with a mean follow-up of 118 weeks. 86.7% of patients demonstrated clinical resolution (absence of pain at the latest follow-up) and 80% of patients demonstrated radiographic resolution. Only one patient sustained a subtrochanteric fracture post-index operation, whilst two others demonstrated redevelopment of cystic architecture on follow-up. Conclusion. This study demonstrates that bone substitute injection is potentially a minimally invasive and seemingly successful technique in the treatment of unicameral bone cysts and other simple bone lesions. Further randomised and comparative studies are required to confirm and validate our findings.